Analysis Of Piston Secondary Motion - Tan, Yeow Chong (2014)
In an internal combustion engme, the piston performs secondary motion besides the primary reciprocating motion. The clearance between the piston skirt and cylinder liner allows the piston to move in the lateral direction and rotational motion about the piston pin axis. The piston secondary motion created impact between the piston skirt and the cylinder liner that radiates unwanted engine noise and increases friction loss. A measurement system consists of three laser displacements sensors are developed to capture the instantaneous piston motion and posture directly from the piston assembly under motorized condition. The laser spots aimed at the piston crown with machined profile in order to obtain the rotational and lateral motion of the piston. The instantaneous piston motion showed that the likelihood of contact between the piston skirt and the cylinder liner increases with the occurrence of the piston secondary motion. In addition, a non-linear model of the piston with reciprocating, lateral and rotational degree of freedom is developed to investigate the piston secondary motion and the piston slap induced vibration behavior of the single cylinder engine.